Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/feduc.2019.00091
|View full text |Cite
|
Sign up to set email alerts
|

Students at the Center: Insights and Implications of Authentic, 5E Instruction in High School English Language Arts

Abstract: This paper explores the 5E model of lesson design (engage, explore, explain, extend, evaluate) in English Language Arts (ELA) classrooms in consideration of an authentic teaching and learning framework. This quasi-experimental pre and post-intervention study centers on student motivation and academic emotions regarding direct instruction in comparison to an authentic, 5E lesson. When comparing pre and post conditions across two types of instructional methods (direct instruction and authentic, 5E lessons), fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Few PEPs also utilized PERMA with all elements infused with the notion of character strengths (Norrish et al, 2013, Green et al, 2021. On the other hand, the 5E model, which was first designed for the teaching of science (Bybee et al, 2006), is now being utilized in other subjects as well (Yeni et al, 2017;Patel, 2019;Jeter et al, 2019). It is a data-driven, research-based approach that describes learning as an internal, learner-guided process and is founded on the principles of constructivism.…”
Section: Integrated Model For Positive Pedagogy In the Context Of Con...mentioning
confidence: 99%
“…Few PEPs also utilized PERMA with all elements infused with the notion of character strengths (Norrish et al, 2013, Green et al, 2021. On the other hand, the 5E model, which was first designed for the teaching of science (Bybee et al, 2006), is now being utilized in other subjects as well (Yeni et al, 2017;Patel, 2019;Jeter et al, 2019). It is a data-driven, research-based approach that describes learning as an internal, learner-guided process and is founded on the principles of constructivism.…”
Section: Integrated Model For Positive Pedagogy In the Context Of Con...mentioning
confidence: 99%
“…Several researchers have also developed the pedagogy of art and design (Orr, Yorke, and Blair 2014;Giralt and Varela 2018;Schaab, Adams, and Coetzee 2022). It has been observed that guiding students is easier through art and design (Jeter et al 2019). Art and design promote students' knowledge seeking attitude (Kisida, Goodwin, and Bowen 2020).…”
Section: Figure 6 Top Publication Regions In Art and Design Publicationmentioning
confidence: 99%
“…When teaching thematic mapping, the ever-increasing availability of high-quality geospatial data, along with rapidly evolving map-making technology, necessitates finding the correct balance of age-old concepts and cutting-edge technologies and trends. (Jeter et al 2019) In the context of an authentic teaching and learning paradigm, this study investigates the 5E model of lesson design (engage, explore, explain, extend, and evaluate) in English Language Arts (ELA) classes. This quasiexperimental pre-and post-intervention research compares direct instruction to a genuine 5E lecture in terms of student motivation and academic feelings.…”
Section: Author-yearmentioning
confidence: 99%
“…Dikemukakan beberapa alasan penggunaan Framework 5E untuk mendesain pembelajaran. 5E memungkinkan inquiry-based teaching di mana siswa berperan aktif dalam mencari dan menemukan informasi sendiri (Jeter et al, 2019). Dengan demikian, 5E dapat memfasilitasi pembelajaran aktif di mana guru berperan sebagai fasilitator dengan siswa sebagai pihak yang secara aktif berperan dalam proses pembelajaran mereka (Jeter et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified